2012
DOI: 10.7150/ijms.4682
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Prediction Model for Success of Vaginal Birth after Cesarean Delivery in Japanese Women

Abstract: Aim: To validate a previously developed prediction model for vaginal birth after cesarean (VBAC) using a Japanese cohort.Methods: We performed a cohort study of all term pregnant women with a vertex position, singleton gestation, and one prior low transverse cesarean delivery attempting a trial of labor between April 1985 and March 2010. Variables necessary for the prediction of successful VBAC were maternal age, pre-pregnancy body mass index, ethnicity, prior vaginal delivery, prior VBAC, and indication for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 18 publications
6
42
4
1
Order By: Relevance
“…23 Yokoi et al also concluded that the best predictor for a successful VBAC was a previous VBAC in their study of 664 women with one previous Caesarean delivery. 24 To the best of the authors' knowledge, this study is the first of its kind to be conducted in Oman. The Sultan Qaboos University Hospital was one of the first centres in Oman to induce labour using a Foley catheter in cases of previous Caesarean delivery; the majority of other centres in Oman use prostaglandins for the induction of labour.…”
Section: Discussionmentioning
confidence: 99%
“…23 Yokoi et al also concluded that the best predictor for a successful VBAC was a previous VBAC in their study of 664 women with one previous Caesarean delivery. 24 To the best of the authors' knowledge, this study is the first of its kind to be conducted in Oman. The Sultan Qaboos University Hospital was one of the first centres in Oman to induce labour using a Foley catheter in cases of previous Caesarean delivery; the majority of other centres in Oman use prostaglandins for the induction of labour.…”
Section: Discussionmentioning
confidence: 99%
“…We have found one study on predictive factors affecting the outcome of VBAC from India [11], three Israeli publications [12,14,17], and one Japanese study [21]. Four publications were applicable for European settings.…”
Section: Commentsmentioning
confidence: 98%
“…Some models have been externally validated or supplemented with new variables in subsequent publications [2,[18][19][20][21]. To our knowledge, the most utilized model originates from the Grobman et al's study [8], considering only factors available at the first prenatal visit.…”
Section: Introductionmentioning
confidence: 99%
“…Ao analisarmos os aspectos relacionados à variável idade materna, dois estudos merecem citação: o de Yokoi et al 21 no Japão, e o de Tan et al 22 na Malásia, que, ao estudarem as taxas de PVPC, não identificaram associação entre a idade materna e os demais resultados. No nosso estudo, gestantes adolescentes apresentaram taxas de PVPC, resultado semelhante ao citado por Pires et al 23 .…”
Section: Discussionunclassified